2020
DOI: 10.20944/preprints202001.0383.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Importance of the Submerged Zone during Dry Periods to Nitrogen Removal in a Bioretention System

Abstract: Adding a submerged zone (SZ) is deemed to promote denitrification during dry periods and thus improve NO3--N removal efficiency of a bioretention system. However, few studies had investigated the variation of nitrogen concentration in the SZ during dry periods and evaluated the effect of the variation on nitrogen removal of the bioretention system. Based on the experiment in a mesocosm bioretetion system with SZ, this study investigated the variation of nitrogen concentration of the system under 17 consecutive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The saturated zone is intended to allow high hydraulic conductivity while providing adequate moisture for plant growth and denitrification processes (Kavehei et al 2019). Several studies showed that a saturated zone and/or C source layer, can enhance N removal through denitrification (Dietz and Clausen 2006, He et al 2020, Lee et al 2013, Peterson et al 2015, Wang et al 2018, Zhang et al 2011. A permanently saturated zone at the bottom of a basin is designed to create anaerobic soil conditions to enhance denitrification.…”
Section: Design Implications For Tn Accumulation and Denitrification ...mentioning
confidence: 99%
“…The saturated zone is intended to allow high hydraulic conductivity while providing adequate moisture for plant growth and denitrification processes (Kavehei et al 2019). Several studies showed that a saturated zone and/or C source layer, can enhance N removal through denitrification (Dietz and Clausen 2006, He et al 2020, Lee et al 2013, Peterson et al 2015, Wang et al 2018, Zhang et al 2011. A permanently saturated zone at the bottom of a basin is designed to create anaerobic soil conditions to enhance denitrification.…”
Section: Design Implications For Tn Accumulation and Denitrification ...mentioning
confidence: 99%